Chemical sensors : simulation and modeling. - Korotchenkov, G. S. (Gennadiĭ Sergeevich) (Sensor technology series., 2012)
This is the third of a new five-volume comprehensive reference work that provides computer simulation and modeling techniques in various fields of chemical sensing and the important applications for chemical sensing such as bulk and surface diffusion, adsorption, surface reactions, sintering, conductivity, mass transport, and interphase interactions.